External validation of International Prognostic Score for asymptomatic early stage chronic lymphocytic leukaemia and proposal of an alternative score - Smolej, Lukáš; Turcsányi, Peter; Kubová, Zuzana; Zuchnická, Jana; Mihályová, Jana; Šimkovič, Martin; Vodárek, Pavel; Krčméryová, Mária; Móciková, Heidi; Brejcha, Martin; Špaček, Martin; Czech CLL Study Group (British journal of haematology, 2021)
Most patients with chronic lymphocytic leukaemia (CLL) are nowadays diagnosed without any symptoms and do not require therapy. A prognostic score identifying patients within this large group who are at high risk of disease progression would be highly beneficial. The recently published International Prognostic Score for Early asymptomatic patients (IPS-E) uses combination of absolute lymphocyte count (ALC) >15 × 109 /l, palpable lymphadenopathy, and unmutated immunoglobulin heavy-chain variable-region (IGHV) gene to predict the time to first-line therapy (TTFT). Patients at low, intermediate, and high risk had estimated 5-year TTFT of 8%, 28%, and 61%. We performed an external validation of the IPS-E score using an unselected, consecutive group of 130 Binet A patients. The 5-year TTFT was 11%, 36%, and 78% (C-statistic 0·74). Furthermore, we propose an alternative system (AIPS-E) using cytogenetic aberrations instead of palpable lymphadenopathy. This system yielded 5-year TTFT of 14%, 40%, and 72%. These results were externally validated in 388 Binet A patients from five Czech centres; the 5-year TTFT was 16%, 37%, and 80% (C-statistic 0·74). In conclusion, we have successfully validated the IPS-E score for patients with early stage CLL. In addition, we propose a modified scoring system, the AIPS-E, combining IGHV, fluorescence in situ hybridisation, and ALC.
Keywords: senioři; Disease Progression; počet lymfocytů; Palpation; prognosis; IGHV; hybridizace in situ fluorescenční; palpace; progrese nemoci; Prognosis; Česká republika; Cohort Studies; mužské pohlaví; Genes, Immunoglobulin Heavy Chain; Czech Republic; kohortové studie; In Situ Hybridization, Fluorescence; time to first-line therapy; Lymphocyte Count; chronic lymphocytic leukaemia; Neoplasm Staging; chronická lymfatická leukemie; FISH; ženské pohlaví; prognóza; Time-to-Treatment; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Chromosome Aberrations; chromozomální aberace; rizikové faktory; staging nádorů; Lymphadenopathy; Female; Aged; Risk Factors; lymfadenopatie; čas zasáhnout při rozvinutí nemoci; výzkumný projekt; Research Design; geny pro těžké řetězce imunoglobulinů; lidé; Male